2007
DOI: 10.2174/1874428100701010005
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of α2-Adrenergic Receptor Agonist Dexmedetomidine on Hemodynamic Response in Direct Laryngoscopy

Abstract: Background: In anesthesia practices, the prevention of sympathetic discharge is important. Dexmedetomidine is a sedative with anxiolytic and analgesic effects. However, its effects on hemodynamic response in direct laryngoscopy are not clear. Objectives: This study aimed to compare the effects of dexmedetomidine with well-known premedication agent midazolam. Methods: Intramuscular 0.05mgkg-1 midazolam (GroupM) or intravenous 1 gkg-1 dexmedetomidine (GroupD) was applied to cases who were scheduled for direct la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In our study the mean SBP, mean DBP, mean MAP decreased in both the study groups after premedication (Table no. 6,7,8). There was statistically significant reduction in systolic and diastolic blood pressure and mean arterial blood pressure in group A as compared to group B at 5, 10, 15, 20, 25 and 30 min after premedication (p value < 0.05).In our study, peripheral arterial SpO2 and RR were compared in both groups (Table no.…”
Section: Anxiety Score:-mentioning
confidence: 51%
“…In our study the mean SBP, mean DBP, mean MAP decreased in both the study groups after premedication (Table no. 6,7,8). There was statistically significant reduction in systolic and diastolic blood pressure and mean arterial blood pressure in group A as compared to group B at 5, 10, 15, 20, 25 and 30 min after premedication (p value < 0.05).In our study, peripheral arterial SpO2 and RR were compared in both groups (Table no.…”
Section: Anxiety Score:-mentioning
confidence: 51%
“…The main disadvantage of IV dexmedetomidine is that sedative action is more pronounced than analgesic effect with profound bradycardia and hypotension [ 18 ]. Moreover, rapid IV dexmedetomidine infusion may cause biphasic alteration of MAP, which is undesirable in anesthesia [ 17 , 19 ]. To minimize these adverse effects, alternative routes of dexmedetomidine were under trial.…”
Section: Discussionmentioning
confidence: 99%
“…30 Berrin et al 2007 and Turan et al 2008 have similarly shown the advantageous effects of Dexmedetomidine during intubation and extubation respectively. 31,32 Hsu YW et al 2004 elicited that Dexmedetomidine, at 0.6-1.2 ng/ml plasma concentration, simulated natural sleep with intact hypercapnic ventilatory response, significant reduction in apnoea-hypopnoea index with intact hypercapnic arousal phenomenon; thereby, changes in paCO 2 and minute ventilation was found comparable to baseline. 33 Yacout AG et al 2012 assessed recovery profile by measuring tracheal extubation time, time to eye opening and time to following verbal commands which were longer in group D relative to group P but with no statistically significant difference between both groups.…”
Section: Bi Spectral Index Monitormentioning
confidence: 99%